Issues in the use of wood as an energy source in the northeastern US - Munson, J.S. (ed.) (Brookhaven National Lab., Upton, NY (USA). National Center for Analysis of Energy Systems, 1980)
This report analyzes some of the concerns surrounding the use of wood for energy in the Northeast. It reviews the information on resource availability and ownership patterns in the Northeast, then focuses on New England, to assess the affect of potential resource constraints on the supply of wood available for energy and the effects of wood energy use on land use patterns. Finally, the application of specific technologies in settings that may experience significant wood energy use in the future is considered, including an assessment of the regional employment and income benefits of a major woodfuel installation.